Beyond the Water's Edge: How Political Parties Influence Foreign Policy Formulation in Belgium. Issue 4 (31st May 2016) - Joly, Jeroen; Dandoy, Régis
Abstract: Based on the growing scholarly recognition of domestic influences on foreign policy, political parties are considered to be among the main drivers behind foreign policy in most parliamentary democracies. In order to understand party influences on the governmental foreign policy agenda, we examine what determines the congruence between party manifestos and the ensuing government agreements in Belgium from 1978 to 2008. We find that a combination of variables related to political parties' negotiation position during government formation and regarding their ideological left-right position co-determine their impact on the content of the coalition agreement in terms of foreign policy priorities. This study shows that political parties differ in their foreign policy priorities and that they compete to see these priorities included in the future government's policy program.